SHALLOW MOONQUAKES AND LARGE SHALLOW EARTHQUAKES: A TEMPORAL CORRELATION - Shirley J.H. (My University, 1986)
The structure and seismicity of the Moon is very different from that of the Earth. One point of similarity is that statistics of seismic energy release in both bodies are dominated by the largest shallow-focus events. This study presents evidence of a relationship linking the timing of the 28 known shallow moonquakes with the timing of the 26 largest shallow earthquakes occurring in the same years (1971–1976). Distributions of the geocentric ecliptic longitude of the Moon λm for the time of occurrence of the lunar and terrestrial seismic events were analyzed both separately and in combination, for the entire 6-year period and for individual years, with the following results:(1)|Statistically significant clustering is present in the series of λm for the times of the earthquakes and moonquakes for the entire sample period (random probability = 0.0036) and for 2 of the 6 individual years (random probabilities ⩽ 0.02).(2)|Phases of the separate lunar and terrestrial seismic event λm distributions for the 6-year period differ by less than 7°. Phases of the earthquake and moonquake distributions are found in the same quadrant of the range in 5 of the 6 individual years.(3)|Annual levels of shallow-focus seismic activity in the Earth and Moon vary in concert in the years 1971–1976.